ANALYSIS OF MARKET STRUCTURE, CONDUCT AND PERFORMANCE OF COPRA IN PARIGI – MOUTONG REGENCY - Hendra Kurniawan; Ratya Anindita; Silvana Maulidah (Agricultural Socio-Economics Journal, 2021)
This study aims to find out and investigate how copra farmers receive in Parigi – Moutong Regency. In this study the data used is primary data and secondary data, primary data is taken using questionnaire list. This research uses IHH and CR4 analysis approach, with the aim to find out the market share and market formed in each copra marketing institution in Parigi – Moutong Regency. The results of the research showed from the results of the analysis conducted is the market formed in copra farmers institutions are a perfect competition market, in the institution of traders collectors (middlemen) market formed is a monopoly market, just as the market formed in large traders is also monopoly. The cr4 value obtained is farmers by 30.82%, collectors by 100%, large traders by 100%. From the results obtained the structure of the market is already affecting the market counduct copra, where the merchant become the determinant haraga copra is a collector to be the recipient of the price.in addition, traders do bond in terms of capital (dwon paymen).Copra market performance is inefficient, where copra farmers in Parigi – Moutong are more dominant in selling copra in three marketing lines that have many marketing agencies involved, with a margin of Rp 2,000. referring to the results, it is fair that the weak still of farmers reaching the market information, especially prices, as a result of the share received by farmers is low. Related to this, there needs to be strengthening in farmers institutions related to copra marketing system.